2019
DOI: 10.3389/fmicb.2019.02117
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of a T Cell Infiltrate in Human Ganglia Years After Herpes Zoster and During Post-herpetic Neuralgia

Abstract: Varicella-zoster virus (VZV) is a human herpesvirus which causes varicella (chicken pox) during primary infection, establishes latency in sensory ganglia, and can reactivate from this site to cause herpes zoster (HZ) (shingles). A major complication of HZ is a severe and often debilitating pain called post-herpetic neuralgia (PHN) which persists long after the resolution of the HZ-associated rash. The underlying cause of PHN is not known, although it has been postulated that it may be a consequence of immune c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The pro-inflammatory effects of VZV-specific T cells may contribute to lesion and HZ pain, severity and duration. Human autopsy studies reveal the trigeminal ganglia, a site of VZV latency and reactivation, contains T cells abutting neurons after the resolution of HZ supporting a potential for local antigen-reactive T cells to contribute to PHN pathogenesis 42 . VZV-specific T cells persisting after HZ resolution may also aid host defense against future episodes of HZ in the same dermatome, as seen in murine studies with HSV, whereby local skin CD8 T RM provide anatomically restricted protection against reinfection 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory effects of VZV-specific T cells may contribute to lesion and HZ pain, severity and duration. Human autopsy studies reveal the trigeminal ganglia, a site of VZV latency and reactivation, contains T cells abutting neurons after the resolution of HZ supporting a potential for local antigen-reactive T cells to contribute to PHN pathogenesis 42 . VZV-specific T cells persisting after HZ resolution may also aid host defense against future episodes of HZ in the same dermatome, as seen in murine studies with HSV, whereby local skin CD8 T RM provide anatomically restricted protection against reinfection 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain represents a common clinical disease [21][22][23] . Peripheral nerve disorders can cause chronic pain, such as diabetes, uremia, neuralgia after herpes zoster, and ischemic neuropathy [38][39][40][41] . However, the pathogenesis, disease progression, and the effectiveness and appropriate duration of treatments remain unclear and difficult to assess 2,12,24,26,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies were able to identify CD8 1 cells as one of the major cell groups infiltrating ganglia after or during zoster infection. 18,41,42 Today, it is known that VZV antigens induce Tcell-mediated immune responses. 24,36 In a murine spinal model, Cao et al reported that T-lymphocyte-deficient mice presented a reduction in injury-induced hypersensitivity, suggesting T lymphocytes as an important factor for the maintenance of neuropathic pain.…”
Section: Cytotoxic T Cells and Sensitizationmentioning
confidence: 99%